Pengembangan E-modul Berbasis Project Based Learning Pada Mata Pelajaran Instalasi Penerangan Listrik Siswa Kelas XI Di Sekolah Menengah Kejuruan - Apri Yenni; Abna Hidayati; Rahmi Pratiwi; Reni Kurnia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop a Project Based Learning E-Module on the Electrical Lighting Installation subject for class XI of SMK which is valid and practical to use in the learning process. This study uses the R&D research method using the 4D development model consisting of four stages, namely define, design, develop and dissemination. The product trial was conducted on 23 class XI TITL students of SMK Negeri 2 Sijunjung and 1 class XI IPL subject teacher. The validity test was carried out by 1 material expert and 2 media experts. Data collection techniques used validation sheets, practicality questionnaires, and media distribution questionnaires. The results of the assessment from the validator and students, namely the assessment of the material aspect by the material expert obtained a score of 3.95, included in the very good category. Furthermore, the assessment of the media by media expert 1 obtained a score of 3.94, included in the very good category. Furthermore, the assessment from media expert 2 obtained a score of 3.75, included in the very good category. In line with the assessments conducted by material and media experts, the e-module received a score of 85.12% from 23 students, a score of 93.6% from 5 teachers, and a score of 86.93% from 12 questionnaire respondents, which categorized it as very practical. The overall assessment of the e-module concluded that the resulting learning media product was excellent and practical for use in the learning process.